2009
DOI: 10.1017/s1461145709009997
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally regulated and thalamus-selective induction of leiomodin2 gene by a schizophrenomimetic, phencyclidine, in the rat

Abstract: The onset of schizophrenia and the schizophrenomimetic effects of an N-methyl-D-aspartate (NMDA) receptor antagonist, ketamine, rarely occur during infancy and childhood, suggesting that schizophrenia-related neuron circuits and molecules in the brain might show an age-related response to an NMDA receptor antagonist. By using a DNA microarray technique, we have identified the developmentally regulated PCP-inducible gene leiomodin2 (Lmod2) that encodes a tropomyosin-binding actin-capping protein enriched in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 56 publications
(59 reference statements)
1
30
0
Order By: Relevance
“…This view also fits with the previous observation (Takebayashi et al, 2009) that an acute PCP injection significantly elevated the Lmod2 gene mRNA levels Fig. 5 Effects of acute injection of MAP on mrt3 expression in developing rat neocortex.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This view also fits with the previous observation (Takebayashi et al, 2009) that an acute PCP injection significantly elevated the Lmod2 gene mRNA levels Fig. 5 Effects of acute injection of MAP on mrt3 expression in developing rat neocortex.…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, the postnatal development of the effects of MAP on the mrt3 expression is more likely to be related to that of the interconnections among the neocortical cells and/or of the molecular cascades that can receive increased dopamine signals via the D1 receptor. It is of interest to note that mrt3 shares the developmental features with mrt1 , CCN1 (Ito et al, 2007), SAP97 (Hiraoka et al, 2010) and Lmod2 (Takebayashi et al, 2009) in that the expressional alterations in responses to schizophrenomimetics occur after the critical period based on the pharmacological models of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain an insight into the molecular basis of the onset, we have focused our attention on the fact that both schizophrenia and similar psychoses induced by NMDA-type glutamate receptor antagonists, such as phencyclidine (PCP) and ketamine, or by dopamine agonists, such as amphetamines and cocaine, usually emerge after adolescence. Moreover, adult-type behavioral disturbances following the application of NMDA receptor antagonists or dopamine agonists in rodents, which are recognized as models of schizophrenia, are observed after a critical period at around 3 postnatal weeks [1]–[3]. These clinical and experimental observations suggest that schizophrenic symptoms and psychotomimetic effects of NMDA receptor antagonists and dopamine agonists may require the maturation of certain brain neuron circuits and molecular networks specifically dysregulated in schizophrenia and their animal homologues.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of Lmod1 was found as a result of steroid induction in human trabecular meshwork cells (Clark et al 2013). It was demonstrated that phencyclidine (a dissociative drug) induction resulted in up-regulation of Lmod2 in the thalamus of rat brain (Takebayashi et al 2009). The authors proposed that the expressional change in the level of thalamic Lmod2 is caused by the drug involvement for regulating psychological and motor function, which eventually causes age-dependent onset of drug-induced schizophrenia.…”
Section: Tropomodulinmentioning
confidence: 99%
“…Further experiments are necessary to clarify how certain Tmod and Lmod isoforms appear in cells and tissues, where they are normally not expressed (Takebayashi et al 2009; Moyer et al 2010; Clark et al 2013). …”
Section: Tropomodulinmentioning
confidence: 99%